The New Use of Technology by the Consular Offices of Romania - Lucica TUDORAN (Communications of International Proceedings, 2023)
Technology is the center of the post COVID-19 activity, private, public or mixed. At the consular offices of Romania, after the request of citizens, technology was included to solve efficiently current administrative tasks. This study aims to show a review of the conditions meant to favorite the good use of technology in the consular activity, to name those technologies, to evaluate if there is now enough information for a good accomplishment of the organization's purpose and to make propositions of progress. Even though there are not so many bibliographic sources at this time on the Romanian consular technology matters (or any, except general concepts about the public administration), this study will be based on an analyze inspired above all on public documents and legislation, but also an interpretation made of my professional point of view. Objective opinions about technology will be considered, the way that this one is actually used by the Romanian consular offices, to answer the question about if there are redundancies and whether those ones can be eliminated by using new processes, activities or other informatics ways.
Keywords: technology; consular; services; redundancies